Chemical conversion pre-treatment liquid, method for producing washed aluminium substrates, method for producing etched aluminium substrates, method for producing electrode materials for aluminium electrolytic capacitors, and method for producing aluminium electrolytic capacitors

JP2025024357APending Publication Date: 2025-02-20KUNIMINE IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023128401
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-07
Publication Date
2025-02-20

Smart Images

  • Figure 2025024357000001
    Figure 2025024357000001
  • Figure 2025024357000002
    Figure 2025024357000002
Patent Text Reader

Abstract

To provide a chemical conversion pre-treatment liquid that can be effectively used in the production of electrode materials for higher capacitance aluminium electrolytic capacitors.SOLUTION: The chemical conversion pre-treatment liquid is produced by dispersing smectite.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a chemical conversion pretreatment liquid, a method for producing a cleaned aluminum base material, a method for producing an etched aluminum base material, a method for producing an electrode material for an aluminum electrolytic capacitor, and a method for producing an aluminum electrolytic capacitor. [Background technology]

[0002] Aluminum substrates are used for electrodes of capacitors and wiring for various electronically conductive circuits, etc. When manufacturing capacitors, the surface area of ​​the aluminum substrate is increased by performing etching treatments, etc., using chemical, physical, or electrochemical methods in order to increase the capacitance. As a method for increasing the surface area of ​​an aluminum substrate as much as possible while still being suitable for use in a capacitor, a direct current etching method capable of forming deep tunnel-shaped holes (pits) in the depth direction of the substrate is known. As an etching solution used in the etching process, for example, Patent Document 1 discloses an electrolytic etching solution composition used for electrochemically etching an aluminum-containing substrate to form pits in the substrate, the electrolytic etching solution composition containing 10 to 70 mass% in total of at least one selected from the group consisting of acetic acid and lactic acid, 0.1 to 10 mass% of aluminum chloride, and water. Patent Document 2 discloses an etching method for aluminum foil for electrolytic capacitors, which includes a first step of electrochemically etching with a direct current in an aqueous solution containing at least chloride ions, a second step of electrochemically etching with a direct current in an aqueous solution containing at least chloride ions and sulfate ions, and a third step of electrochemically or chemically etching in an aqueous solution containing nitrate ions or chloride ions, and is characterized in that through-pits are formed in the first step, non-through-pits are formed in the second step, and the already-formed pits are enlarged in the third step. In this document, various aqueous solutions containing chloride ions are used as etching solutions before chemical conversion. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2018-119184 A [Patent Document 2] Japanese Patent Application Publication No. 8-264391 Summary of the Invention [Problem to be solved by the invention]

[0004] The inventions described in the above patent documents contain an acid capable of dissolving aluminum, which is an amphoteric metal. The dissolution of aluminum by acid has almost no location selectivity. Therefore, when an acid is contained in the etching solution that is the chemical pretreatment solution, the chemical pretreatment solution dissolves the aluminum base material in the surface layer of the contact hole, which causes a problem that the pit depth cannot be made deep and the surface area is difficult to be made sufficiently large. Furthermore, halogen ions, such as chloride ions, contained in etching solutions, which are used as pretreatment solutions, attack the oxide film on the surface, generating the starting points for pit formation and promoting pitting corrosion. In particular, AC etching uses inhibitors such as sulfuric acid and nitric acid to regenerate the film and repeatedly generate the starting points for pit formation, creating complex shapes and achieving a higher surface enlargement ratio. On the other hand, if the aluminum base material is not sufficiently cleaned and halogen ions such as chloride ions remain on the aluminum base material when it is moved to the next chemical conversion step, the formation of an aluminum oxide layer by the chemical conversion treatment may be inhibited, and the voltage resistance may be deteriorated.

[0005] An object of the present invention is to provide a chemical pretreatment liquid that enables the production of an electrode material for an aluminum electrolytic capacitor having a higher capacitance. Another object of the present invention is to provide a method for producing a cleaned aluminum substrate using the above-mentioned chemical pretreatment liquid, and a method for producing an etched aluminum substrate. Another object of the present invention is to provide a method for producing an electrode material for an aluminum electrolytic capacitor, and a method for producing an aluminum electrolytic capacitor, by anodizing an aluminum base material produced using the above-mentioned chemical pretreatment liquid. [Means for solving the problem]

[0006] As a result of intensive research, the present inventors have found that an electrode material for an aluminum electrolytic capacitor having a larger electrostatic capacity can be obtained by performing a cleaning treatment and / or an etching treatment with a chemical pretreatment liquid containing smectite, which is a type of clay mineral, to increase the surface area expansion ratio, and then performing a chemical conversion treatment on the etched substrate. The present invention was completed through further research based on these findings.

[0007] That is, the above-mentioned object of the present invention has been achieved by the following means. [1] A chemical pretreatment liquid containing dispersed smectite. [2] The chemical pretreatment liquid according to [1] above, for use as a cleaning liquid. [3] The chemical pretreatment liquid according to [1] above, for use as an etching liquid. [4] The chemical pretreatment liquid according to any one of the above [1] to [3], wherein the smectite is synthetic smectite. [5] The chemical pretreatment liquid according to any one of the above [1] to [4], wherein the smectite content is 0.1 to 20 mass %. [6] The chemical conversion pretreatment liquid according to any one of the above [1] to [5], for treating an aluminum base material. [7] A method for producing a cleaned aluminum substrate, comprising cleaning an aluminum substrate with the chemical conversion pretreatment liquid according to [2] above. [8] A method for producing an etched aluminum substrate, comprising etching an aluminum substrate with the chemical conversion pretreatment liquid according to [3] above. [9] A method for producing an etched aluminum substrate, comprising cleaning an aluminum substrate with the chemical conversion pretreatment liquid described in [2] above, and etching the resulting cleaned aluminum substrate with the chemical conversion pretreatment liquid described in [3] above.

[10] A method for producing an electrode material for an aluminum electrolytic capacitor, comprising etching the cleaned aluminum base material obtained by the method for producing an aluminum electrolytic capacitor according to [7] above, and anodizing the etched aluminum base material obtained.

[11] A method for producing an electrode material for an aluminum electrolytic capacitor, comprising anodizing an etched aluminum base material obtained by the method according to [8] or [9] above.

[12] A method for producing an aluminum electrolytic capacitor, comprising incorporating the electrode material for an aluminum electrolytic capacitor obtained by the method for producing an aluminum electrolytic capacitor according to

[10] above as an anode of the aluminum electrolytic capacitor.

[13] A method for producing an aluminum electrolytic capacitor, comprising incorporating the electrode material for an aluminum electrolytic capacitor obtained by the production method according to

[11] above as an anode of the aluminum electrolytic capacitor. Effect of the Invention

[0008] According to the chemical conversion pretreatment liquid, the method for producing a cleaned aluminum base material, the method for producing an etched aluminum base material, the method for producing an electrode material for an aluminum electrolytic capacitor, and the method for producing an aluminum electrolytic capacitor of the present invention, it is possible to obtain an electrode material for an aluminum electrolytic capacitor having a larger electrostatic capacitance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, preferred embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments except as defined in the present invention.

[0010] [Pretreatment solution for chemical conversion] One embodiment of the present invention is a chemical pretreatment liquid in which smectite is dispersed. The chemical pretreatment liquid can be used, for example, as a cleaning liquid or an etching liquid. For example, as a cleaning liquid, it can be used to remove dirt and degrease an aluminum substrate. In addition, as an etching liquid, it can be used to electrolyze an aluminum substrate, forming deep tunnel-shaped holes (pits) in the depth direction of the substrate to increase the surface area, or forming holes with more complex shapes to achieve a high surface area expansion ratio.

[0011] If the chemical pretreatment solution of the present invention is used as a cleaning solution for an aluminum substrate, smectite will adhere to the aluminum oxide film while performing cleaning treatment such as degreasing, and the edge parts of the clay layer of the adhered smectite will partially dissolve the aluminum oxide film, which is believed to increase the number of attack points of halogens and increase the pit density per unit area when performing etching treatment following the cleaning treatment. As a result, it is possible to manufacture a capacitor with high withstand voltage and high capacitance through chemical conversion treatment after etching treatment. The chemical pretreatment liquid of the present invention is also suitable as an etching liquid for metal substrates. For example, the constituent metal of the substrate to be etched can be aluminum, aluminum alloys, other valve metals, etc., if an electrode material for a capacitor is to be obtained. The type of metal to be combined with aluminum that constitutes an aluminum alloy is not particularly limited. By using the chemical pretreatment liquid of the present invention, a substrate made of aluminum or an aluminum alloy can be effectively etched, and an electrode material for an aluminum electrolytic capacitor with desired characteristics can be obtained.

[0012] (Aluminum base) In the present invention and this specification, the term "aluminum substrate" (hereinafter also simply referred to as "substrate") is not particularly limited as long as it is a metal whose main component is aluminum. For example, pure aluminum (aluminum with a purity of 99% or more, preferably with a purity of 99.9% or more, and more preferably with a purity of 99.99% or more) or an aluminum alloy whose main component is aluminum can be used. When the aluminum substrate is used as an electrode material for an aluminum electrolytic capacitor, the substrate can have a shape of, for example, a foil, plate, or wire, and can also be formed into a molded body using these.

[0013] (Pretreatment solution) The chemical pretreatment solution of the present invention is a composition containing smectite and water (dispersion medium) as essential components. The smectite component makes the chemical pretreatment solution alkaline, so that it can be used as a cleaning solution for degreasing. In addition, it adheres to the aluminum oxide film, and the edge parts of the clay layer of the adhered smectite partially dissolve the aluminum oxide film, which is thought to increase the number of attack points of the halogen in the subsequent etching process, thereby making it possible to increase the pit density per unit area. In addition, when the chemical pretreatment liquid of the present invention is used as an etching liquid, it is considered that the periphery of the pit opening entrance of the surface layer of the aluminum substrate is covered with smectite, which suppresses chemical or electrochemical elution of that portion and makes it possible to increase the aspect ratio of the pit as viewed from the cross section of the substrate (in other words, to deepen the depth of the tunnel). In addition, when etching is performed by DC electrolysis, it is also possible to increase the number of pitting corrosion origins on the surface in the thickness direction of the substrate, which is considered to increase the pit density per area and make the substrate area larger. As a result, it is possible to manufacture an etched substrate with a large electrostatic capacity suitable as a raw material member for electrode materials for aluminum electrolytic capacitors. In addition, even when etching is performed by AC electrolysis, it is considered that the number of pitting corrosion origins on the surface can be increased, and a more complex shape can be generated, which increases the surface area of ​​the aluminum substrate and increases the electrostatic capacity.

[0014] (Smectite) The type of smectite contained in the chemical pretreatment solution of the present invention is not particularly limited and can be appropriately selected depending on the purpose. Smectite can be either natural or synthetic, but synthetic smectite is particularly preferred because it is a material that contains as little chlorine-based impurities as possible. The smectite is preferably one or more selected from montmorillonite, beidellite, nontronite, saponite, hectorite, sauconite, and stevensite, and more preferably one or more selected from hectorite, saponite, and stevensite.

[0015] The interlayer cation species of the smectite used in the present invention is not particularly limited. From the viewpoint of completely swelling in the chemical pretreatment liquid, dispersing with a smaller particle size, covering the periphery of the pit opening with a narrow area to suppress the elution of aluminum therefrom, and making the pit deeper, smectite containing sodium or lithium, which is a cationic species, as an interlayer cation is particularly preferred. In addition, from the viewpoint of higher water swelling, the cation exchange capacity (CEC) of the smectite is preferably 20 meq / 100 g or more, more preferably 25 meq / 100 g, and particularly preferably 30 meq / 100 g. Moreover, the particle size of the smectite (the size of dispersed particles in the chemical pretreatment liquid) is preferably 1 nm to 500 μm, more preferably 5 nm to 400 μm, and even more preferably 10 nm to 300 μm, from the viewpoint of further suppressing the elution of the aluminum substrate by the smectite.

[0016] In addition to the above-mentioned reasons, the following is also believed to be the reason why the capacitance is improved by obtaining an electrode material for an aluminum electrolytic capacitor using the chemical pretreatment liquid of the present invention containing smectite. Known general etching solutions contain relatively high concentrations of halogen ions such as chlorine. This is because halogen anions are particularly prone to pitting corrosion, and therefore tend to form tunnel-shaped pit structures suitable for increasing the surface area. However, if halogen ions remain that have not been completely washed away, it becomes difficult to generate aluminum oxide for the dielectric layer in the next chemical conversion step, which can cause a problem of not being able to increase the capacitance. Among smectites, synthetic smectite in particular does not contain chlorine-containing compounds in the manufacturing raw materials. Therefore, it is essentially free of chlorine ions and is less likely to inhibit the production of aluminum oxide in the chemical conversion process. Furthermore, it is thought that the interlayer cations (e.g., sodium) contained in smectite interact with halogens remaining during etching treatment, forming alkali halides such as sodium chloride, which makes it easier to efficiently remove the residual halogens from the system during water washing. Furthermore, it is believed that smectite itself also interacts specifically with metals and metal oxides to roughen the surfaces of various metals and partially form pits. This action is believed to be the reason why a high specific surface area can be obtained by etching without the use of chloride ions, and it does not adversely affect the subsequent chemical conversion treatment.

[0017] (water) The chemical pretreatment solution of the present invention contains water as an essential component (dispersion medium). There is no particular limitation on the water used, and distilled water, ion-exchanged water, etc. are preferred from the viewpoint of not containing impurities such as chlorine ions. The ionic conductivity of the water is preferably 10 μS / m or less, more preferably 5 μS / m or less, and even more preferably 1 μS / m or less.

[0018] (pH of chemical pretreatment solution) There is no particular limit to the pH of the chemical conversion pretreatment liquid of the present invention. When only smectite, in which the interlayer metal is sodium or lithium, is dispersed in water, the pH is generally in the weak alkaline range of about 10 to 11. The chemical conversion pretreatment liquid may be used as is, or the pH may be adjusted to a neutral to acidic range by adding an acid component, which is often contained in an etching liquid, which is an electrochemical conversion pretreatment liquid. Examples of known electrochemical conversion pretreatment liquids include sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid, and these may be used in combination.

[0019] (Concentration of smectite components in chemical pretreatment solution) There is no particular restriction on the concentration of the smectite component in the chemical pretreatment liquid of the present invention. From the viewpoint of achieving the desired effects in cleaning and etching treatments and exhibiting appropriate fluidity, the content of smectite in the chemical pretreatment liquid is preferably 0.1 to 20 mass %, more preferably 0.3 to 15 mass %, and particularly preferably 0.5 to 10 mass %.

[0020] <Other ingredients> The chemical pretreatment solution of the present invention may contain other components within the range that does not impair the effects of the present invention. For example, in order to facilitate the progress of the etching treatment, the solution may contain various salts having a supporting electrolyte function that can increase the etching efficiency when present in the electrolysis method, in addition to various acid and alkali components. Other additives may be added, such as a stabilizer, an antifoaming agent, a pH adjuster, a specific gravity adjuster, a viscosity adjuster, a wettability improver, a chelating agent, an oxidizing agent, a reducing agent, an organic solvent, and a surfactant. The other additives may be used alone or in combination of two or more. The content of the additives in the chemical pretreatment liquid is preferably 0.01 to 10 mass% per additive so as not to impede the effect of the smectite on the etching treatment.

[0021] [Method of manufacturing cleaned aluminum substrate] A method of using the chemical conversion pretreatment liquid of the present invention as a cleaning liquid (hereinafter, sometimes simply referred to as a "cleaning treatment method") includes a step of cleaning an aluminum substrate with the above-mentioned chemical conversion pretreatment liquid to obtain a cleaned substrate.

[0022] The conditions for cleaning using the chemical conversion pretreatment liquid of the present invention are not particularly limited, and normal conditions can be applied. The temperature is preferably such that the chemical conversion pretreatment liquid exists stably as a liquid and has high cleaning efficiency. Specifically, the temperature is preferably 4°C to 90°C, more preferably 10°C to 80°C, and most preferably 20°C to 70°C. Furthermore, when the chemical conversion pretreatment liquid of the present invention is used without an additive, it often exhibits weak alkalinity. When it is desired to clean a component that is difficult to remove with a weak alkaline component, a known and commonly used acid cleaning step may be added. In order to fully exert the effects due to the smectite in the chemical pretreatment solution of the present invention, it is preferable to carry out the acid washing step before washing with the chemical pretreatment solution of the present invention. In addition, ultrasonic application, stirring, etc. may be appropriately carried out to improve the efficiency of washing.

[0023] [Method of manufacturing etched aluminum substrate] A method of using the chemical conversion pretreatment liquid of the present invention as an etching liquid (hereinafter, may also be simply referred to as an "etching method") includes a step of etching an aluminum substrate with the above-mentioned chemical conversion pretreatment liquid to obtain an etched substrate.

[0024] The conditions for etching using the chemical pretreatment liquid of the present invention are not particularly limited, and normal conditions can be applied. The temperature is preferably a temperature at which the chemical pretreatment liquid is stable as a liquid and a sufficient number of pits are generated. Specifically, the temperature is preferably 25 to 95°C, more preferably 40 to 90°C, and even more preferably 60 to 80°C. In addition, when etching is performed by direct current electrolysis using the chemical pretreatment solution of the present invention, the current and voltage may be appropriately controlled so as to achieve the conditions for forming pits of the desired shape on the surface of the substrate. The current density during etching is 0.1 to 100 mA / cm. 2 It is preferable to set the current within the range of 0.5 to 50 mA / cm 2The etching voltage (Vf) is usually set within a range of 2 to 800V, preferably within a range of 5 to 700V, and more preferably within a range of 8 to 650V. The chemical pretreatment solution of the present invention can also be used for AC etching by AC electrolysis as an etching treatment for manufacturing a low-voltage, high-capacity capacitor. The preferred ranges of current and voltage are the same as those for the DC electrolysis. There is no particular restriction on the frequency range, but it is preferably 500 to 5000 Hz, and more preferably 1000 to 3000 Hz. After etching is completed, it is recommended to wash with distilled water, ion-exchanged water, etc., so as not to adversely affect the next chemical conversion process.

[0025] In the etching method using the chemical pretreatment liquid of the present invention, the entire substrate may be etched, or only a portion of the substrate may be etched. When forming pits by etching in a portion of the substrate surface, the portion to be etched may be selected in advance by a method such as photoresist.

[0026] The pretreatment solution of the present invention can be used as a cleaning solution in the cleaning step, or as an etching solution in the etching step, or can be used in both steps.

[0027] The method for producing a cleaned aluminum substrate of the present invention can be achieved by the above-mentioned cleaning method. Also, the method for producing an etched aluminum substrate of the present invention can be achieved by the above-mentioned etching method.

[0028] [Method of manufacturing electrode material for aluminum electrolytic capacitors] The method for producing an electrode material for an aluminum electrolytic capacitor of the present invention includes a step of performing a chemical conversion treatment by anodization on a substrate obtained by etching the cleaned aluminum substrate obtained by the above-described method for producing a cleaned substrate, or on an etched aluminum substrate obtained by the method for producing an etched substrate, to obtain a chemically treated substrate having an aluminum oxide film formed on its surface.

[0029] [Manufacturing method of aluminum electrolytic capacitors] The method for producing an aluminum electrolytic capacitor of the present invention includes incorporating the above-described chemically treated substrate as an anode of an aluminum electrolytic capacitor.

[0030] (chemical treatment) In the present invention, chemical conversion treatment means that the substrate obtained in each embodiment of the present invention is immersed in a chemical conversion solution and then chemical conversion treatment is performed by anodization. This chemical conversion treatment forms a layer of aluminum oxide coating on the surface of the aluminum substrate, and an electrode material for aluminum electrolytic capacitors can be obtained. Anodization is generally performed by direct current electrolysis, but there are no particular limitations on the current and voltage conditions, and the anodization is performed within the known general range.

[0031] (chemical liquid) The chemical conversion liquid may be a known chemical conversion liquid used in the chemical conversion process of aluminum electrolytic capacitors. For example, an aqueous solution of ammonium borate, ammonium phosphate, or organic acid ammonium may be used. The smectite contained in the chemical conversion pretreatment liquid of the present invention may also be used as one component of the chemical conversion liquid. Furthermore, the chemical conversion pretreatment liquid of the present invention itself may be used as the chemical conversion liquid.

[0032] By using the above-mentioned electrode material for aluminum electrolytic capacitors, an aluminum electrolytic capacitor can be manufactured. The above-mentioned capacitor equipped with the electrode material for aluminum electrolytic capacitors can be manufactured by a known method, except for using the above-mentioned electrode material for aluminum electrolytic capacitors. The aluminum electrolytic capacitor generally further includes an electrolytic solution, a separator, electrolytic paper, and the like. EXAMPLES

[0033] The materials used in this example were as follows: (Each smectite) Hectorite: Sumecton-SWN (trade name), cation exchange capacity 43meq / 100g Saponite: Sumecton-SA (trade name), cation exchange capacity 66meq / 100g Stevensite: Sumecton-ST (trade name), cation exchange capacity 25meq / 100g In both cases, the interlayer ions are sodium ions, manufactured by Kunimine Kogyo Co., Ltd. (Other electrolytes) Nitric acid, sulfuric acid, hydrochloric acid, sodium hydroxide Both are premium grade and manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. (chemical liquid) Ammonium adipate Special grade, Fujifilm Wako Pure Chemical Industries, Ltd.

[0034] Example 1 As the chemical pretreatment liquid, a dispersion having the composition shown in Table 1 was obtained by dispersing hectorite in distilled water (electrical conductivity 0.2 μS / cm or less) to a concentration of 5 mass %.

[0035] (Cleaning process) The aluminum substrate used was an aluminum foil with a thickness of 120 μm, a purity of 99.99% or more (4N), and a (100) plane occupancy rate of 90%. 2A flag-shaped electrode was prepared by connecting aluminum foil without cutting it to supply power to the electrode, and this was used as an aluminum substrate. This aluminum substrate was immersed in the above-mentioned chemical pretreatment solution at room temperature for 10 minutes, and then washed three times with distilled water to obtain a washed aluminum substrate washed with the chemical pretreatment solution. The washed aluminum substrate was then subjected to chemical conversion treatment via DC etching according to the following step A, or chemical conversion treatment via AC etching according to the following step B.

[0036] <Process A> (DC etching process) A 0.4 mol / L aqueous hydrochloric acid solution was prepared as an etching solution for DC etching. A stainless steel container (Sus304) with an inner diameter of 30 mm was filled with the etching solution, and only the electrode portion of the cleaned aluminum substrate obtained in the cleaning process was immersed in the etching solution. The aluminum substrate and the stainless steel container corresponding to the counter electrode were connected to a DC power source (Takasago Manufacturing Co., Ltd., HV-1.5-03) and a digital multi-tester for measuring current and voltage (manufactured by Sanwa Electric Instruments Co., Ltd., model number: RD701), and the bath temperature was set to 70°C and the current density to 0.5 mA / cm. 2 The etching treatment was carried out for 300 seconds under the conditions described above. After the etching treatment, the substrate was washed three times with pure water and then dried to obtain an etched aluminum substrate.

[0037] (Conversion treatment process after DC etching treatment) A 0.05 mol / L ammonium adipate solution was prepared as the chemical conversion solution. Only the electrode portion of the etched aluminum substrate obtained by the DC etching process was immersed in the chemical conversion solution. The aluminum substrate and a stainless steel container corresponding to the counter electrode were connected to a high voltage power supply (Takasago Manufacturing Co., Ltd., HV-1.5-03) and a digital multi-tester for measuring current and voltage (Sanwa Electric Instruments Manufacturing Co., Ltd., model number: RD701), and the bath temperature was 25°C and the current density was 1 mA / cm. 2 The chemical conversion treatment was carried out under the above conditions until the voltage reached 10 V, thereby obtaining a chemically-treated aluminum substrate.

[0038] <Process B> (AC etching process) Instead of a DC power supply, a potentiostat / galvanostat (Hokuto Denko Corporation, HA-151B) was connected as an AC power supply, and a bath temperature of 70°C and a triangular wave with a frequency of 1000 Hz and a current density of 0.3 mA / cm were applied. 2 The cleaned aluminum substrate was subjected to AC etching in the same manner as in the DC etching process, except that the etching was performed for 200 seconds under the conditions of: After the etching, the substrate was washed three times in pure water and then dried to obtain an etched aluminum substrate.

[0039] (chemical conversion treatment process after AC etching treatment) The etched aluminum substrate was subjected to chemical conversion treatment in the same manner as in the chemical conversion treatment step after the DC etching treatment, except that the ultimate voltage was 7 V, to obtain a chemically treated aluminum substrate.

[0040] (Examples 2 to 4 and Comparative Example 1) Each chemically treated aluminum substrate was obtained in the same manner as in Example 1, except that a chemical pretreatment liquid having the composition shown in Table 1 was used as the chemical pretreatment liquid.

[0041] Each of the resulting chemically treated aluminum substrates was evaluated by the following evaluation methods, and the results are shown in Table 1 below.

[0042] (Evaluation of electrostatic capacitance of chemical conversion film) The electrostatic capacitance was evaluated for the chemically treated aluminum substrates (aluminum substrates on which an oxide film was formed by chemical treatment) of Examples 1 to 4 and Comparative Examples 1 and 2. Using a 15% by mass aqueous solution of ammonium adipate previously prepared as an electrolyte, the electrostatic capacitance C of each chemical conversion film was measured using an LCR meter (NF Corporation, model number: ZM2355) based on the electrostatic capacitance test method for low-voltage etching foils under conditions of a frequency of 120 Hz, a measurement voltage of 0.5 Vrms, and a bias voltage of 1.5 V.

[0043] (Evaluation of chemical coating withstand voltage) The chemically treated aluminum substrates of Examples 1 to 4 and Comparative Examples 1 and 2 were subjected to re-chemical conversion treatment using the same operation and conditions. In this treatment step, the voltage value immediately after the start of the re-chemical conversion treatment was taken as the coating withstand voltage (V) and was used as an index of the withstand voltage of the capacitor.

[0044] (Evaluation of the electricity storage capacity of chemical conversion films) The CV product was calculated from the capacitor evaluation results for the etching solution compositions used in Examples 1 to 4 and Comparative Examples 1 and 2. The CV product was calculated by multiplying the capacitance C obtained by the above measurement by the film withstand voltage (V). This value was used as an index of the electricity storage capacity of the capacitor.

[0045] [Table 1]

[0046] As shown in Table 1, electrolytic capacitors (Examples 1 to 4) having an aluminum oxide film produced by etching and chemical conversion treatment using a cleaned aluminum base material obtained by cleaning the aluminum base material with the chemical conversion pretreatment liquid of the present invention, which is an aqueous dispersion of smectite, showed high capacitance values ​​both in DC etching and AC etching. Furthermore, the aluminum electrolytic capacitors of Examples 1 to 4 showed a 7 to 40% increase in capacitance compared to the capacitors of Comparative Examples 1 and 2, which were obtained by cleaning the aluminum base material with a chemical conversion pretreatment liquid not containing smectite, followed by etching and chemical conversion treatment.

[0047] Example 5 As the chemical pretreatment liquid, a dispersion having the composition shown in Table 2 was prepared by dispersing hectorite in distilled water (electrical conductivity 0.2 μS / cm or less) to a concentration of 5 mass %.

[0048] (Cleaning process) The aluminum substrate used was an aluminum foil with a thickness of 120 μm, a purity of 99.99% or more (4N), and a (100) plane occupancy rate of 90%. 2A flag-shaped electrode was prepared by connecting aluminum foil without cutting it as a power supply to this electrode, and used as an aluminum substrate. This aluminum substrate was immersed in a 1M aqueous sodium hydroxide solution at room temperature for 10 minutes to remove surface oil and the like. After washing in pure water three times, it was neutralized in a 1M aqueous nitric acid solution, washed in pure water three times again, and then dried to obtain a washed aluminum substrate. The washed aluminum substrate was subjected to chemical conversion treatment via a DC etching treatment according to the following step C, or chemical conversion treatment via an AC etching treatment according to the following step D.

[0049] <Process C> (DC etching process) A stainless steel container (Sus304) with an inner diameter of 30 mm was filled with the chemical pretreatment solution, and only the electrode portion of the cleaned aluminum substrate obtained in the cleaning process was immersed in the chemical pretreatment solution. The aluminum substrate and the stainless steel container corresponding to the counter electrode were connected to a high-voltage power supply (Takasago Manufacturing Co., Ltd., HV-1.5-03) and a digital multi-tester for measuring current and voltage (Sanwa Electric Instruments Manufacturing Co., Ltd., model number: RD701), and the bath temperature was set to 70°C and the current density to 0.5 mA / cm. 2 The etching treatment was carried out for 300 seconds under the conditions described above. After the etching treatment, the substrate was washed three times with pure water and then dried to obtain an etched aluminum substrate.

[0050] (Conversion treatment process after DC etching treatment) A 0.05 mol / L ammonium adipate solution was prepared as the chemical conversion solution. Only the electrode portion of the etched aluminum substrate obtained by the DC etching process was immersed in the chemical conversion solution. The aluminum substrate and a stainless steel container corresponding to the counter electrode were connected to a high voltage power supply (Takasago Manufacturing Co., Ltd., HV-1.5-03) and a digital multi-tester for measuring current and voltage (Sanwa Electric Instruments Manufacturing Co., Ltd., model number: RD701), and the bath temperature was 25°C and the current density was 1 mA / cm. 2 The chemical conversion treatment was carried out under the above conditions until the voltage reached 10 V, thereby obtaining a chemically-treated aluminum substrate.

[0051] <Process D> (AC etching process) Instead of a DC power supply, a potentiostat / galvanostat (Hokuto Denko Corporation, HA-151B) was connected as an AC power supply, and a bath temperature of 70°C and a triangular wave with a frequency of 1000 Hz and a current density of 0.3 mA / cm were applied. 2 The cleaned aluminum substrate was subjected to AC etching in the same manner as in the DC etching process, except that the etching was performed for 200 seconds under the conditions of: After the etching, the substrate was washed three times in pure water and then dried to obtain an etched aluminum substrate.

[0052] (chemical conversion treatment process after AC etching treatment) The etched aluminum substrate was subjected to chemical conversion treatment in the same manner as in the chemical conversion treatment step after the DC etching treatment, except that the ultimate voltage was 7 V, to obtain a chemically treated aluminum substrate.

[0053] (Examples 6 and 7, Comparative Examples 3 and 4) Each chemically treated aluminum substrate was obtained in the same manner as in Example 5, except that a chemical pretreatment liquid having the composition shown in Table 2 was used as the chemical pretreatment liquid.

[0054] (Examples 8 and 9) Each chemically treated aluminum substrate was obtained in the same manner as in Example 5, except that a chemical pretreatment liquid having the composition shown in Table 2 was used as the chemical pretreatment liquid. In Example 8, 50 g of an aqueous dispersion of hectorite at a concentration of 1% by mass was prepared, and 50 g of an aqueous solution of 0.7 mol / L nitric acid was mixed with this while stirring with a stirrer to prepare a chemical pretreatment liquid. In Example 9, 50 g of an aqueous dispersion of stevensite at a concentration of 2% by mass was prepared, and 50 g of an aqueous solution of 1.0 mol / L sulfuric acid was mixed with this while stirring with a stirrer to prepare a chemical pretreatment liquid.

[0055] The electrostatic capacitance, the withstand voltage of the coating, and the charge storage capacity of the chemical conversion film of each of the obtained chemically converted aluminum substrates were evaluated by the above-mentioned evaluation methods. The results are shown in Table 2 below.

[0056] [Table 2]

[0057] As shown in Table 2, the aluminum electrolytic capacitors (Examples 5 to 9) produced by chemical conversion treatment using etched substrates that had been subjected to DC etching and AC etching treatment using the chemical pretreatment solution of the present invention as an etching solution showed higher capacitance than the capacitors (Comparative Examples 3 and 4) that had been subjected to chemical conversion treatment after etching with a solution that did not contain smectite.

Claims

1. A chemical pretreatment liquid containing dispersed smectite.

2. 2. The chemical conversion pretreatment solution according to claim 1, which is used as a cleaning solution.

3. 2. The chemical pretreatment solution according to claim 1, which is used as an etching solution.

4. The chemical pretreatment solution according to any one of claims 1 to 3, wherein the smectite is a synthetic smectite.

5. The chemical pretreatment liquid according to any one of claims 1 to 3, wherein the smectite content is from 0.1 to 20 mass %.

6. The chemical conversion pretreatment liquid according to any one of claims 1 to 3, for treating an aluminum substrate.

7. A method for producing a cleaned aluminum substrate, comprising cleaning an aluminum substrate with the chemical conversion pretreatment liquid according to claim 2.

8. A method for producing an etched aluminum substrate, comprising etching an aluminum substrate with the pretreatment liquid according to claim 3.

9. 5. A method for producing an etched aluminum substrate, comprising cleaning an aluminum substrate with the chemical conversion pretreatment liquid according to claim 2, and etching the resulting cleaned aluminum substrate with the chemical conversion pretreatment liquid according to claim 3.

10. A method for producing an electrode material for an aluminum electrolytic capacitor, comprising etching the cleaned aluminum base material obtained by the method according to claim 7, and anodizing the etched aluminum base material obtained.

11. A method for producing an electrode material for an aluminum electrolytic capacitor, comprising anodizing the etched aluminum base material obtained by the method according to claim 8 or 9.

12. A method for producing an aluminum electrolytic capacitor, comprising incorporating the electrode material for an aluminum electrolytic capacitor obtained by the production method according to claim 10 as an anode of the aluminum electrolytic capacitor.

13. A method for producing an aluminum electrolytic capacitor, comprising incorporating the electrode material for an aluminum electrolytic capacitor obtained by the production method according to claim 11 as an anode of the aluminum electrolytic capacitor.

Citation Information

Patent Citations

  • Etching of aluminum foil for electrolytic capacitor

    JP1996264391A

  • Electrolytic etching solution composition, electrolytic etching method, electrolytically etched base material, electrode material for aluminum electrolytic capacitor, and capacitor

    JP2018119184A